ASSESSMENT OF GROUNDWATER QUALITY FOR IRRIGATION AT MALAMAWI ISLAND, BASILAN, PHILIPPINES - Alejandro Amin Jalil; Roger A Luyun, Jr; Aurelio A Delos Reyes, Jr; Victorino A Bato (Center for Implementation of Standards for Environmental and Forestry Instruments Solo, 2020)
ABSTRACTThe assessment of groundwater quality for agricultural purposes was conducted in Malamawi Island, Isabela City, Basilan. Groundwater quality wasevaluated based on the FAO irrigation quality standards (1994)which include salinity and alkalinity, sodium, magnesium, bicarbonate hazards and chloride hazards. Spatial delineation of groundwater quality parameters was carried out using QGIS software. Results revealed that the use of groundwater from two separate sampling wells (SW4 and SW6) in Lukbuton area require slight to moderate restrictionbased on the parameters of electrical conductivity and magnesium hazard. This means that its groundwater can still be safe for irrigation but with little salinity hazard on sensitive crops.Also, the chloride concentration in SW4 indicates that groundwater was slightly poor in quality but generally suitasble for irrigation while in SW6, the calcium concentration was considered unsuitable for irrigation. In the same way, the sampling wells 1 and 3 in Santa Barbara and Lukbuton were considered unsafe and unsuitable for irrigation in terms of magnesium hazard. Also, the calcium content of groundwater in some part of the island was considered unsuitable for irrigating high-value crops. Therefore, this study suggests that some management is needed in the northeastern part of Lukbuton because of its poor ground water quality for irrigation in terms of salinity. Keywords: Malamawi, Basilan, irrigation, shallow well. ABSTRAK Penilaian kualitas air tanah untuk keperluan pertanian dilakukan di Pulau Malamawi, Kota Isabela, Basilan. Kualitas air tanah dievaluasi berdasarkan kesesuaian untuk irigasi sesuai standar kualitas irigasi FAO meliputi salinitas dan alkalinitas, serta bahaya natrium, magnesium, bikarbonat dan klorida. Delineasi spasial dari parameter kualitas air tanah dilakukan dengan menggunakan perangkat lunak QGIS. Hasil penelitian menunjukkan bahwa penggunaan airtanah dari dua sumur sampel terpisah (SW4 dan SW6) di Kawasan Lukbuton memerlukan pembatasan ringan hingga sedang berdasarkan parameter konduktivitas listrik dan bahaya magnesium. Hal ini menunjukkan air tanah masih aman untuk irigasi walaupundengan sedikit bahaya salinitas untuk tanaman yang sen sitif. Selain itu, konsentrasi klorida di SW4 menunjukkan bahwa kualitas airtanah agak buruk walaupun umumnya cocok untuk irigasi sedangkan di SW6, konsentrasi kalsium dianggap tidak sesuai untuk irigasi. Dengan cara yang sama, pengambilan sampel sumur 1 dan 3 di Santa Barbara dan Lukbuton dianggap tidak aman dan tidak cocok untuk irigasi dalam hal bahaya magnesium. Selain itu, kandungan kalsium air tanah di beberapa bagian pulau dianggap tidak sesuai untuk mengairi tanaman bernilai ekonomi tinggi. Oleh karena itu, studi ini menyarankan bahwa perlu dilakukan pengelolaan di bagian timur laut Lukbuton karena kualitas air tanah yang buruk untuk irigasi dari segi salinitas.Kata kunci: Malamawi, Basilan, irigasi, sumur dangkal